Legal Protection for Children Victims of Postpartum Depression - Diyan Shofie Harisnaeni; Irma Cahyaningtyas (LAW REFORM, 2021)
Children are a gift given by God through a woman. The presence of a child certainly raises many new adaptations in family life. The transition period to face a new life turns out to be more or less a problem that results in children; one of which is postpartum depression in a mother. This article aims to examine the forms of legal protection for a child who is a victim of postpartum depression. This article uses a normative juridical approach and secondary data with descriptive analytical research specifications and qualitative analysis. Based on the results of the study, postpartum depression is included in the category of mental illness model caused by the mental illness with clinical depression symptoms that affect psychological conditions ranging from excessive anxiety, neglecting children, to physically injuring children. This form of legal protection for children is stated in Law Number 23 of 2002 in conjunction with Law Number 35 of 2014 concerning Child Protection. Regarding the accountability of perpetrators, for the postpartum depression which reflects on Article 44 of the Criminal Code, it is necessary to have an examination first before determining the responsibility to be imposed to overcome and prevent postpartum depression.